FEMALE FUNCTIONARIES' OPINIONS ON THE COMMUNICATION OF THE GOLKAR BALI PARTY ORGANIZATION TO WELCOME THE 2024 LEGISLATIVE ELECTION - I Gusti Agung Ayu Sri Puspa Dewi (Sean Institute, 2022)
Welcoming the 2024 Simultaneous Elections, the Golkar Bali Party organization as an election participant conducts internal and external organizational communication to increase electability to achieve overall victory in the legislative and presidential elections. This study tried to find out the standpoints of female functionaries who are non-legislators of the Golkar Bali Party and are preparing to participate in the 2024 legislative elections on internal organizational communications. It is not easy to be in an organization alongside legislators who at some points are competitive, especially in the run-up to legislative elections. The internal communication of the organization needs to be researched to find out the opinions of these female functionaries who have the task of raising the Golkar Bali Party, on the other hand, female functionaries are the public relations of political parties. This study analyzes the variations in functionary responses from drawn opinions formed from real experiences and sources of information from the Golkar Bali Party organization. To discuss the problem of this research, qualitative research with a descriptive approach is used. The paradigm of this research is phenomenological. The research tradition used is sociopsychological. Research data sources are obtained from primary sources and secondary sources. Data collection techniques are carried out through several methods, namely, in-person interviews and documentation found on the internet.